PERAN DUKUN BERSALIN TRADISIONAL DALAM PERAWATAN KEHAMILAN, PERTOLONGAN PERSALINAN, PERAWATAN PASCAPERSALINAN DAN KEPERCAYAAN - Lestari Handayani (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
Delivery mortality rate is still considered high. One of the mainreasons is the high rate of delivery assistance conducted by traditional midwives. To anticipate the problems and to obtain safe delivery, the government has decided to enact a program to appoint midwives to work in the villages A study was carried out on trained traditional midwiveswho play their role in the villages in the hope to study their role and development of these midwives in the future. The study was conducted in six villages of two subdistricts in Tulung Agung Regency. An interview and a survey were carried out to six traditional midwives and mothers-of-children-below-five years respectively in the study area. The study shows that 67.1 percent of delivery cases were assisted by traditional midwives. The role of traditional midwives during pregnancy care was considered low, yet was considered high during the delivery itself, the post-partum services, and the belief in relation to pregnancy and delivery. The fact shows there is a considerable healthy relation of social and delivery cooperation assistance between traditional midwives and trained midwives. It is suggested that improvement in knowledge and skills on delivery assistance be intensified. Besides, it is also suggested to improve the role of traditional village midwives to cooperate with trained midwives to guide the former in becoming the agents to convey the health program to its targets.